MODELAGEM DE FORMA DE ONDA PARA PROCESSO GMAW - RITHIELE MACIEL DOS SANTOS , SINARA; MANOEL LENZ VIANNA DA SILVA , JOÃO; DE CAMPOS , MAURÍCIO (Salão do Conhecimento, 2021)
Projeto de pesquisa desenvolvido na Unijuí.